PENGARUH MODEL GDL DISERTAI FEEDBACK TERHADAP HASIL BELAJAR SISWA SMA PADA MATERI HIDROLISIS GARAM - Umarela, Septiawan Hady; Hairida, Hairida; Harun, A. Ifriany (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is based on the students who passive and the monotonous teaching with lecture method from teacher during the learning process so that impacts to the achievement. The purpose of this study is to determine the difference of achievement and the influence of the use of guided discovery learning model with feedback on the students's achievement on the salt hydrolysis material. The form of the research used is quasi experiment with the research design "nonequivalent control group design in the form of pretest-posttest control group design". Samples were selected based on saturated sampling technique, class XI IPA 1 as experimental class and class XI IPA 2 as control class because the UTS grade of experimental class was lower than control class. The data collection tool used consists of a test of achievement consisting of pretest and posttest. Based on the analysis of posttest data with U-Mann-Whitney test obtained Asymp.Sig (2-tailed) of 0.003 < 0.05 which means there are differences in achievement between students using GDL model with feedback with students using conventional models. Calculation of Effect Size with GDL model with feedback gives 33,40% influence to student achievement on salt hydrolysis material grade XI SMA Panca Bhakti Pontianak.          Keywords: GDL with Feedback, achievement, salt hydroliysis